Targeted Synthesis of a Highly Stable Aluminium Phosphonate Metal–Organic Framework Showing Reversible HCl Adsorption - Reichenau, Timm M.; Steinke, Felix; Wharmby, Michael T.; Näther, Christian; Engesser, Tobias A.; Stock, Norbert (Angewandte Chemie International Edition, 2023)
A concept for obtaining isoreticular compounds with tri‐ instead of tetravalent metal cations using highly acidic reaction conditions was developed and successfully applied in a high throughput study using N,N′‐piperazinebis(methylenephosphonic acid) (H4PMP), that resulted in the discovery of a new porous aluminium phosphonate denoted CAU‐60⋅6 HCl. The high‐throughput study was subsequently extended to other trivalent metal ions. Al‐CAU‐60⋅6 HCl demonstrates reversible desorption of HCl (18.3 wt % loading) with three distinct compositions observed with zero, four or six HCl molecules per formula unit. Structural changes were followed in detail by powder X‐ray diffraction, EDX analysis as well as IR spectroscopy. Rapid desorption of HCl in water within minutes and subsequent adsorption from the gas phase and from aqueous solution are shown. Furthermore, it is possible to adsorb HBr into the guest free Al‐CAU‐60 framework, demonstrating the high stability of this compound. Protons make the difference. Highly acidic synthesis conditions were employed to synthesize porous MIII‐phosphonates with different degrees of framework protonation. Rapid release of HCl in solution and re‐adsorption from aqueous solution and from the gas phase is demonstrated and structural changes that accompany these processes are elucidated.